Optimization on the excavation work at Gelang Patah [electronic resource] - Idda Elfazana Albar, 1987-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2011